The Teacher’s Role in Generating and Maintaining the Motivation of Adult Learners of English in a Corporate Environment: A Pilot Study - Kálmán, Csaba (Working Papers in Language Pedagogy, 2015)
It has been confirmed by numerous studies that teachers play a significant role in creating and maintaining the motivation of learners of English as a foreign language (see for example, Dörnyei & Csizér (1998); Mezei & Csizér (2005); Roth et al. (2007); Radel et al. (2010); Dörnyei & Ushioda (2011)). Nevertheless, if we narrow down the scope of inquiry to the motivation of adult learners of English aged between 25 and 60, in an English as a foreign language (EFL) context, we can find very few empirical studies. Some exceptions are Shoaib and Dörnyei’s (2005), Szaszkó’s (2007), and Murray’s (2011) research of adult learners of English. Even though all of the above studies are concerned with the motivation of adult learners, none of them address specifically the teacher’s impact on motivation, let alone in a corporate environment. In order to fill this niche and investigate this impact, two semi-structured interview guides (one for students, and one for human resources managers) were developed, validated, and piloted. The data elicited during the interviews proved that the instruments were valid, and the findings underpin the importance of teacher - learner communication, tailor-made teaching and the professionalism of the teacher in enhancing adult learners’ motivation in a corporate context.